IMPLEMENTING A NEW ALGORITHM FOR ANALYSIS OF PROTOCOL EFFICIENCY USING STABILITY AND DELAY TRADEOFF IN MANET (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper, we present an extensive ns-2.33 simulation basedperformance comparison of four widely known stability-orientedon-demand Mobile Adhoc Network (MANET) routingprotocols. Our simulations show that modified Power DSR(PDSR) routes are more stable than existing DSR routes, whichare more stable than DSDV and AODV routes. This also resultsin an increased packet delivery ratio for PDSR in comparison tothat of DSR and DSDV. On the other hand, based on the energyconsumed per packet and the average energy used per node,DSR is better than DSDV, which is better than PDSR. At lownetwork density and mobility, PDSR routes incur the lowestdelay and as the network density and node mobility increases,DSR incurs lower delay. Thus, we see a stability-delay-energyconsumption tradeoff among these three stability-orientedrouting protocols. Regarding the fairness of node usage, weobserve that routes get distributed more evenly with increase inthe node mobility and network density. But, still there is anappreciable variation in the energy consumption per node asonly the chain of nodes that form stable routes are exhausted to agreater extent. A routing protocol that incurs fewer transitionswill lose fewer data packets, create less routing overhead andalso maintain in-order data delivery. At the same time, bystaying with a long-lived route, the routing protocol may incur alonger end-to-end delay. We intend to explore this tradeoffbetween stability and delay and try to come with up a metric thatwould quantify the efficiency of a MANET routing protocolwith respect to both stability and delay. On these lines, weintroduce the idea of Stability-Delay Tradeoff (SDT) as ameasure of the efficiency of a MANET routing protocols.